OVERVIEW OF THE EAST ASIAN EXPERIENCE RESEARCH AT GREAT DEPTHS ON THE EXAMPLE OF OIL AND GAS BASIN OF SICHUAN (CHINA) - Koryakin, S.Y. (Perm Federal Research Centre Journal, 2016)
Generalized material for deep oil and gas potential and effectiveness of deep and ultra-deep drilling in China. Analyzed the East Asian experience in deep drilling. Proved the importance of deep drilling, as a kind of study of the subsoil in all oil and gas basins with a large capacity of the sedimentary cover.